SAMPLE: A Software Suite to Predict Consolidation and Microstructure for Powder Bed Fusion Additive Manufacturing - Markl, Matthias; Rausch, Alexander; Küng, Vera; Körner, Carolin (Advanced Engineering Materials, 2019)
Powder bed fusion comprises all layer-by-layer additive manufacturing technologies of parts built from a powder bed. To exploit the advantages of near-net shape manufacturing of complex geometries, in contrast to conventional manufacturing techniques, it is essential to understand the underlying physical phenomena occurring during processing for a broad range of different process scenarios. Experimental approaches are costly in time and material and provide only limited access inside the process. However, to understand the process behavior and predict final properties of parts, numerical approaches are powerful tools. This work presents the software suite S𝔸𝕄PLE (Simulation of Additive Manufacturing on the Powder scale using a Laser or Electron beam) which simulates the consolidation and microstructure evolution during beam-based powder bed fusion processes. It is based on a mesoscopic approach, in which statistical powder beds, melt pool dynamics, evaporation effects, and microstructure evolution are considered and can simulate the build-up of more than 100 layers. The underlying models and algorithms of the software including a newly applied thermal model are described. Finally, the unique potential of the software is demonstrated by reviewing the influence of various powder bed properties, the effects of evaporation, and the grain structure evolution in the process.
CRIS-Team Scopus Importer:2019-12-31
Keywords: cellular automaton; lattice Boltzmann methods; numerical simulation software; selective electron beam melting; selective laser melting